Physical Properties of Pineapple Fiber and Mechanical Testing for Scrub Pads Application - สุรวัฒนวิเศษ, วลัยพรรณ; ชลสาคร, ผู้ช่วยศาสตราจารย์ ดร.สาคร; ชลสาคร, ผู้ช่วยศาสตราจารย์ ดร.สาคร; มงคลรัตนาสิทธิ์, ผู้ช่วยศาสตราจารย์ ดร.รัตนพล (Journal of Food Health and Bioenvironmental Science, 2017)
The objectives of this research were to study the mechanical separation of fibers from pineapple leaves and to study the production of the scrub pads from pineapple leaf fiber of different lengths. The raw material was the leaves of Pattavia pineapple in Rayong Province, Thailand. The methodology focused on the study of the separation of pineapple leaf fiber with the semi-automatic fiber separator machine, the physical properties of the pineapple leaf fibers as well as the efficiency of the production of the pineapple leaf fibers and the production of the scrub pads from pineapple leaf fiber by lengths of three, six and nine centimeters. The results found that the characteristics of long section had articulate, rough surfaces. For the cross section, it was found that the fibers had lumens at their diameter. Regarding the physical properties of pineapple leaves fibers, it was found that the average fiber length was 30-50 centimeters, with a tensile strength of 24.95 grams/denier and 34.69 % elongation. For productivity, it was found that one kilogram of fresh pineapples could produced 66 grams of fibers (6.6% of the total products), in 10.35 minutes. The results of the scrub pads production from the three length sizes found that there were five processes the weight scale, lengthwise cutting, pounding, forming and sewing scrub pads are convenient and easy ways to save energy. The result of useful resistance of the scrub pads found that scrub pads from pineapple leaf fibers with a length nine centimeters had the best durability against abrasion (level four) There differences of weight and thickness before and after averaged 0.133 gram and 0.825 mm, respectively.